Preclinical evaluation of CD70-specific CAR T cells targeting acute myeloid leukemia - Wu, Gongqiang; Guo, Shanshan; Luo, Qian; Wang, Xiaoxia; Deng, Wenhai; Ouyang, Guifang; Pu, Jeffrey J.; Lei, Wen; Qian, Wenbin (Frontiers in Immunology, 2023)
Abstract Chimeric antigen receptor (CAR)-T cell therapy has achieved unprecedented success in treating hematopoietic malignancies. However, this cell therapy is hampered in treating acute myeloid leukemia (AML) due to lack of ideal cell surface targets that only express on AML blasts and leukemia stem cells (LSCs) but not on normal hematopoietic stem cells (HSCs). In this study, we demonstrated that CD70 heterogeneously expressed on AML primary cells, including leukemia blasts, leukemic progenitor, and stem cells, but not expressed on normal HSCs and majority of blood cells. We generated a second-generation CD70-specific CAR-T cells using a construct containing a humanized 41D12-based scFv and a 41BB-CD3ζ intracellular signaling domain. This anti-CD70 CAR-T cell exhibited potent cytotoxicity, cytokines production, and proliferation when incubated with CD70+ AML cell lines. It also displayed robust anti-leukemia activity and prolonged survival in Molm-13 xenograft mouse model. However, such CAR-T cell therapy did not completely eliminate leukemia in vivo, suggesting that future studies aiming to generate innovative combinatorial CAR constructs or to increase CD70 expression density on leukemia cell surface to prolong the life-span of CAR-T cells in the circulation will be needed in order to optimize CAR T cell responses for AML. Keywords: CD70, CAR-T, Immunotherapy, Acute myeloid leukemia, leukemia stem cells